The relationship between job satisfaction, organizational commitment and organizational citizenship behavior among secondary school teachers in Katsina state - Yangaiya, Salisu Abba; Mohd Ali, Hairuddin (Tetfund, 2015)
The purpose of this study is to examine the relationship between Job Satisfoction, Organizational Commitment and Organizational Citizenship Behavior: among secondary school teachers in Katsina State Nigeria. The study also examines which among the independent variables (Job Satisfaction and Organizational Commitment) best predicts Organizational Citizenship Behavior The study uses questionnaires to collect the needed data. The uestionnaires wereodopted and adaptedfor this study. In all 370 secondary school teachers were used as sample. Descriptive statistics and multiple regression were used in analyzing the data collected using Statistical Package for Social Science research (^SP^t^,version 20.0. Findings indicate that the two independent variables (Job satisfaction and Organizational Commitment) predict Organizational Citizenship Behavior (OCB) (R'z : .31). Moreoveri among the independent variables Organizational Commitment best predicts Organizational Citizenship Behaviors of secondary school teachers (standardized cofficient : .44). The findings contribute to the existing literature as before now, fa,v studies were conducted on the area in Katsina Stateinparticular and Nigeria in general. As implicationfor this study school managers as well as other stake holders should try aqd enhance school climate, so as to improve teachers' job satisfoction and commitment to enable them exhibit Organizational Citizenship B ehaviors.